ICE handbook of concrete durability : a practical guide to the design of resilient concrete structures - Soutsos, Marios (ICE handbooks, 2023)
ICE Handbook of Concrete Durability, Second edition is a comprehensive practical reference for professionals involved in design and maintenance of concrete structures of all types. With contributions from a range of international experts, the book combines a thorough but accessible exposition of the principles of durable concrete design with a hands-on approach to its application in construction projects. The handbook helps readers to understand the likely causes of deterioration in concrete structures, facilitates the selection of appropriate materials and supports the development of designs that minimise the risks arising from deterioration mechanisms. Extensively revised and updated throughout, this edition includes four new chapters, including chapters on non-destructive testing and structural health monitoring, and lessons learnt by expert witnesses involved in construction disputes, as well as new case studies of durability problems and solutions. Coverage includes * physical and chemical deterioration mechanisms * durability of concretes made with Portland and non-Portland cement-based binders and recycled demolition aggregates * alternative materials to improve concrete durability * performance-based specifications * modelling the effects of deterioration mechanisms * improving construction processes for better durability * repair methods. ICE Handbook of Concrete Durability is an invaluable guide for construction professionals, including design engineers, consultants and contractors, as well as postgraduate students on courses in concrete technology and the design of concrete structures. Marios Soutsos is Professor of Structures/Material in the School of Natural and Built Environment at Queen's University Belfast, UK.